2008
DOI: 10.1158/1078-0432.ccr-07-1430
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Radiographic, and Biochemical Characterization of Multiple Myeloma Patients with Osteonecrosis of the Jaw

Abstract: Purpose: Osteonecrosis of the jaw (ONJ) has been reported in patients with a history of aminobisphosphonate use. This study was conducted in order to define ONJ clinically and radiographically and gain insights into its pathophysiology. Experimental Design: Eleven multiple myeloma (MM) patients with ONJ were included in the study. Patients underwent clinical, biochemical, radiographic, and molecular profiling. Ten MM patients on aminobisphosphonates without ONJ and five healthy volunteers were used as controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
61
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(70 citation statements)
references
References 31 publications
9
61
0
Order By: Relevance
“…preceded oral bone exposure. Recently, Raje et al reported in clinically unaffected sides of the jaws of ONJ patients imaging abnormalities similar to the affected sides [17], a feature shown here in Fig. 1 (patient 3).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…preceded oral bone exposure. Recently, Raje et al reported in clinically unaffected sides of the jaws of ONJ patients imaging abnormalities similar to the affected sides [17], a feature shown here in Fig. 1 (patient 3).…”
Section: Discussionsupporting
confidence: 68%
“…Our observation is in keeping with the pronounced boneseeking-isotope uptake, pointing to the persistence of an effective blood supply to the affected site. Accordingly, no differences in genes associated with angiogenesis were reported in multiple myeloma patients with NBPs related ONJ [17]. Thus, defective local circulation is unlikely to be responsible for the necrosis, contrary to previous deductions [19,30].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This fact has also been emphasised by other authors, especially in regard to the Greek and US population (Raje et al, 2008). We have suggested that it could be an issue of differential susceptibility to ONJ in the Greek population , although careful pretreatment, dental assessment and avoidance of invasive dental procedures, as suggested by the author (Coleman, 2008), could partly account for this difference.…”
Section: Sirsupporting
confidence: 56%
“…Gene expression profiling is a powerful way of understanding the molecular basis of diseases, and has been applied to explore the unique gene expression patterns and distinctly expressed genes of MM from different samples including peripheral blood, bone marrow and isolated cells (9)(10)(11). A number of potential biomarkers pertaining to disease classifications and therapy responses have been identified (5).…”
Section: Introductionmentioning
confidence: 99%